The Potential Role of Polyphenols in Oxidative Stress and Inflammation Induced by Gut Microbiota in Alzheimer's Disease - Umair Shabbir; Akanksha Tyagi; Fazle Elahi; Simon Okomo Aloo; Deog-Hwan Oh (MDPI AG, 2021)
Gut microbiota (GM) play a role in the metabolic health, gut eubiosis, nutrition, and physiology of humans. They are also involved in the regulation of inflammation, oxidative stress, immune responses, central and peripheral neurotransmission. Aging and unhealthy dietary patterns, along with oxidative and inflammatory responses due to gut dysbiosis, can lead to the pathogenesis of neurodegenerative diseases, especially Alzheimer's disease (AD). Although the exact mechanism between AD and GM dysbiosis is still unknown, recent studies claim that secretions from the gut can enhance hallmarks of AD by disturbing the intestinal permeability and blood-brain barrier via the microbiota-gut-brain axis. Dietary polyphenols are the secondary metabolites of plants that possess anti-oxidative and anti-inflammatory properties and can ameliorate gut dysbiosis by enhancing the abundance of beneficial bacteria. Thus, modulation of gut by polyphenols can prevent and treat AD and other neurodegenerative diseases. This review summarizes the role of oxidative stress, inflammation, and GM in AD. Further, it provides an overview on the ability of polyphenols to modulate gut dysbiosis, oxidative stress, and inflammation against AD.